Peran Satuan Polisi Pamong Praja dalam Menyelenggarakan Ketentraman dan Ketertiban Umum di Kabupaten Bengkalis - Ramadhany, Randy (Journal of Social Contemplativa, 2023)
This article aims to increase understanding of the main responsibilities and roles of the Civil Service Police Unit (Satpol PP), with a special focus on the Benkalis district level Satpol PP. Satpol PP is a regional institution formed to enforce regional regulations, maintain peace and order, and ensure community protection. The Satpol PP Post Office in the Regency is under the authority of the Regent and is directly responsible for its operations and administration to the Regional Director. This article focuses on the responsibility of Satpora PP as a facilitator of community welfare and overall progress. Each region has its own characteristics and faces different obstacles, such as the increasing number of informal street vendors, the problem of beggars and people without shelter (PPWS), the presence of food vendors with poor lighting, and the circulation of alcoholic drinks.